A budget impact analysis of adult immunization with tetanus, diphtheria, and pertussis vaccination for the prevention of pertussis in at-risk populations in Colombia - Nurilign Ahmed; Edisson Rodriguez; Victor Saravia; Laura Triana; Jorge A. Gomez (Human Vaccines & Immunotherapeutics)
Pertussis (i.e. whooping cough) is an acute respiratory disease that can cause substantial morbidity and healthcare costs. Patients at higher risk of pertussis may benefit from booster vaccination (Tdap). This study aimed to estimate the budget impact of introducing Tdap into Colombia’s healthcare insurance plan (HCIP) for at-risk adults (asthma, COPD, and HIV) aged ≥ 20 years. For each population, a Microsoft Excel-based model was developed with a five-year time horizon. Demographic inputs were obtained from the United Nations Department of Economic and Social Affairs and the World Bank Group. Epidemiology inputs were from peer-reviewed retrospective studies and systematic reviews of pertussis. Cost inputs were based on 2023 pricing data indexed to consumer price indices. Tdap coverage and market share were assumed as 10% and 74%, respectively. Without Tdap, estimated total five-year medical costs associated with pertussis disease management, in United States dollars ($), were $34.6 million (M), $37.4 M, and $9.3 M, for patients with asthma, COPD, and HIV. Introducing Tdap could avoid 135, 103, and 50 pertussis cases and 8, 9 and 3 hospitalizations due to pertussis in these populations. The total budget impact of Tdap entry into Colombia’s HCIP was $1.3 M, $1.2 M and ~$137 thousand for patients with asthma, COPD, and HIV, respectively. Therefore, introducing Tdap vaccination for adults with asthma, COPD, and HIV in Colombia at just 10% coverage could substantially decrease pertussis disease burden and associated healthcare resource utilization. A proportion of the HCIP budget would be required to protect those at risk.